Impact of high-intensity endurance exercise on regional left and right ventricular myocardial mechanics - Stewart, G.; Chan, J.; Yamada, A.; Kavanagh, J.; Haseler, Luke; Shiino, K.; Sabapathy, S. (OXFORD UNIV PRESS, 2017)
© The Author 2017. Aims Strenuous endurance exercise acutely increases myocardial wall stress and evokes transient functional cardiac perturbations. However, it is unclear whether exercise-induced functional cardiac disturbances are ubiquitous throughout the myocardium or are segment specific. The aim of this study was to examine the influence of high-intensity endurance exercise on global and segmental left (LV) and right (RV) ventricular tissue deformation (strain). Methods and results Echocardiography was used to measure strain in 23 active men (age: 28±2 years; VO 2 peak : 4.5±0.7 L min -1 ) at rest and during a standardized low-intensity exercise challenge, before and after a 90-min high-intensity endurance cycling intervention. Following the cycling intervention, LV and RV global strain decreased at rest (LV: -18.4±0.4% vs.-17.7±0.4%, P < 0.05; RV:-27.6±0.7% vs.-26.4±0.6%, P < 0.05) and by a greater extent during the lowintensity exercise challenge (LV: -21.3±0.4% vs. -19.2±0.5%, P < 0.01; RV: -28.4±0.8% vs.-23.5±0.9%, P < 0.01). Reductions in LV strain were unique to regions of RV attachment (e.g. LV septum: -24.4±0.5% vs.-21.4±0.6%, P < 0.01) with lateral (218.9±0.4% vs. 218.4±0.5%) and posterior segments (-19.5±0.4% vs.-18.8±0.7%) unaffected. Similarly, augmentation of strain from rest to exercise was abolished in the RV free wall (-1.1±1.0% vs. 2.9±1.2%, P < 0.01), reduced in the septum (-4.6±0.4% vs. -2.4±0.5%, P < 0.01), and unchanged in the lateral (-1.2±0.6% vs. -0.9±0.6%) and posterior walls (-1.7±0.6% vs. -1.3±0.7%). Conclusion Changes in ventricular strain following high-intensity exercise are more profound in the right ventricle than in the left ventricle. Reductions in LV strain were unique to the septal myocardium and may reflect ventricular interactions secondary to exercise-induced RV dysfunction.